2016
DOI: 10.1620/tjem.239.315
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Thrombomodulin Ameliorates Ischemia-Reperfusion Injury of Liver Grafts by Modulating the Proinflammatory Role of High-Mobility Group Box 1

Abstract: Transplantation using grafts obtained after cardiac death (CD) is considered a promising solution for graft shortages. However, no standard criteria for organ preservation have been established for CD donors. High-mobility group box 1 (HMGB1) is a DNA-binding protein that is released from dying hepatocytes as an early mediator of inflammation and organ tissue damage. HMGB1 stimulates immunocytes to produce inflammatory cytokines, thereby amplifying the inflammatory response. Thrombomodulin is an integral membr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…In previous reports, rTM and other treatments were generally administered before the onset of ischemia 7,12‐14,17,23,40‐44 . The IR insult was also more profound in genetically modified mice lacking the N‐terminal lectin‐like domain of TM 21,22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous reports, rTM and other treatments were generally administered before the onset of ischemia 7,12‐14,17,23,40‐44 . The IR insult was also more profound in genetically modified mice lacking the N‐terminal lectin‐like domain of TM 21,22 .…”
Section: Discussionmentioning
confidence: 99%
“…rTM has been utilized clinically in Japan for the treatment of disseminated intravascular coagulation (DIC) by an activity promoted by domain 2 11 . There are many reports that suggest that the administration of rTM might ameliorate IR‐induced damage in various organs 12‐17 . We have previously reported that rTM blocked HMGB‐1 binding to TLR‐4, which was followed by suppression of nuclear factor kappa B (NF‐κB)–induced inflammation and diminished levels of IR‐induced liver injury in mice 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Negrath et al , 43 using various defatting cocktails, showed that successful defatting was associated with improved recovery from IRI. 43 Preconditioning of livers on the NMP circuit with Nodosin, 44 as well as with thrombomodulin, 45 was also associated with improvement in endothelial damage and in IRI.…”
Section: Pre-clinical Studiesmentioning
confidence: 97%
“…A recent study investigated the impact of recombinant soluble thrombomodulin, which can bind HMGB1 and prevent HMGB1-mediated proinflammatory responses, on IRI in liver grafts. Thrombomodulin treatment attenuated levels of HMGB1 and inflammatory cytokines, decreased markers of liver graft injury, and improved organ function (104). Other studies suggest that HA production may be an actionable target.…”
Section: Implications For Damps In Sot Therapiesmentioning
confidence: 98%